(3GdSjGSI GdfbOjI hESJbdGdjI GdHfc GdeQcRj (B/s - (3YHO GdMejO, YHO GdeWdHs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2013)
(3fXQI ELeGdjI ddSjGSI GdfbOjI(B- (3GdSjGSI GdfbOjI aj EWGQ GdfXQjGJ GdEbJUGOjI GdeNJdaI(B- (3JMdjd CgOGa GdSjGSI GdfbOjI(B- (3OhQ GdSjGSI GdfbOjI aj JMbjb GdESJbQGQ hGdJhGRf GdfbOj hGdEbJUGOj(B- (3GdJVNe, CSHGHg hBKGQg GdEbJUGOjI(B- (3GdSjGSI GdfbOjI hYdGL GdJVNe(B- (3YdGL GdJVNe ef NdGd SjGSGJ GdJKHjJ hGdEUdGM Gdgjcdj(B- (3aYGdjI GdSjGSI GdfbOjI aj EbJUGOGJ GdOhd GdeJbOeI(B- (3aYGdjI GdSjGSI GdfbOjI aj EbJUGOGJ GdOhd GdfGejI(B-(3EbJUGOjGJ GdHfhc GdeGdjI(B- (3ESJbdGdjI GdHfc GdeQcRj hGdSdGeI GdeUQajI(B- (3eaghe ESJbdGdjI GdHfc GdeQcRj heYGjjQgG hOQLGJgG(B- (3ESJbdGdjI GdHfc GdeQcRj bHd hHYO GdNUNUI(B- (3JMdjdGJ GdSjGSI GdfbOjI aj eUQ NdGd GdaJQI (B1991-2011s
Keywords: (3GdEbJUGO GdfbOjs; (3GdHfc GdeQcRjs; (3GdSjGSI GdfbOjIs